CHANGING OF THE ALTAI GLACIER SYSTEM SINCE THE MID-TWENTIETH CENTURY AND ITS RESPONSE TO THE CLIMATE WARMING IN FUTURE - V. M. Kotlyakov; Xie Zichu; Wang Shuhong; Wang Xin; T. Y. Khromova; G. A. Nosenko (Лëд и снег, 2015)
Characteristics of the Altai glacier system are analyzed on the data from Chinese and Former Soviet Union glacier inventories. Two glacier data sets, recent remote sensing data and the glacier inventories data were compared. It has been found that 208 glaciers disappeared and the glacial area decreased by 12%. Functional models of the glacier system variations have been developed using the equation of relationship between an annual glacier ablation and a mean summer temperature; the glacier system structure and behavior of the equilibrium line altitudes at the steady state were taken into account as well. The models were used to study response of the glacial runoff to a climatic change. The model results show that, under the climate warming scenario of 0.05°С/year, only 3% Altai glaciers inChinaand 9% inRussiawill remain by the end of this century.